How to show that every Boolean ring is commutative?

A ring $R$ is a Boolean ring provided that $a^2=a$ for every $a \in R$. How can we show that every Boolean ring is commutative?

Solutions Collecting From Web of "How to show that every Boolean ring is commutative?"

Every Boolean ring is of characteristic 2, since $a+a=(a+a)^2=a^2+a^2+a^2+a^2=a+a+a+a\implies a+a=0$.
Now, for any $x,y$ in the ring
$x+y=(x+y)^2=x^2+xy+yx+y^2=x+y+xy+yx$, so $xy+yx=0$ and hence $xy+(xy+yx)=xy$. But since the ring has characteristic 2, $yx=xy$.

I always like to know where these problems come from, their history. This was first proved in a paper by Stone in 1936. Here’s a link to that paper for anyone who is interested:

His proof is in the first full paragraph on p. 40.

Of course, this is an old chestnut: if you are interested in typical generalizations of this commutativity theorem in a wider, more structural context (to associative, unitary rings) I suggest reading T.Y. Lam’s beautiful Springer GTM 131 “A First Course in Noncommutative Rings”, Chapter 4, §12, in particular the Jacobson-Herstein Theorem (12.9), p. 209: A (unitary, associative) ring $R$ is commutative iff for any $a,b\in R$ one always has $(ab-ba)^{n+1}=ab-ba$ for some $n\in\mathbb N$ ($n$ generally depending on $a,b$). (Further, using Artin’s theorem concerning diassociativity of alternative algebrae, associativity of $R$ may be weakened to alternativity.) Cp. also the exercises given, in particular Ex. 9. Note that the Boolean case is special, as that the ring considered needn’t be unitary a-priori. Kind regards – Stephan F. Kroneck.

Plug $a = x + y$.

HINT $\rm\quad\ \ A = X+Y\ \ \Rightarrow\ \ X\ Y = – Y\ X\:.\$ But $\rm -1 = 1\$ via $\rm\ A = -1$

As Yuval points out $(x+y)^{2} = x+y$ which implies $x^{2} + y^{2} + x \cdot y + y \cdot x = x+y$. Now from this you have $x \cdot y + y \cdot x =0$.

We want to show that $xy = yx$ for all $x,y \in R$. We know that $(x+y)^2 = x+y$. So $(x+y)^2 = (x+y)(x+y) = xx+xy+yx+yy = x+xy+yx+y = x+x^2y^2+y^2x^2+y$. This equals $x+(xy)+(yx) + y = x+y$ so that $xy = yx$.

When you get to the part where ab=-ba
ab =-ba (1)
Pre-multiply a to both sides
a(ab)=a(-ba)
a^2b=a-ba
ab=a-ba (2)
Post-multiply a to (1)
(ab)a=(-ba)a
aba=-ba^2
aba=-ba (3)
.
.
.
From (2) & (3), you can deduce that ab=ba

If $a,b\in R$,
\begin{align}
2ba
&=4ba-2ba\\
&=4(ba)^2-2ba\\
&=(2ba)^2-2ba\\
&=2ba-2ba\\
&=0,
\end{align}
so
\begin{align}
ab
&=ab+0\\
&=ab+2ba\\
&=[ab+ba]+ba\\
&=[(a+b)^2-a^2-b^2]+ba\\
&=[(a+b)-a-b]+ba\\
&=0+ba\\
&=ba.
\end{align}